2016
DOI: 10.1016/j.enbuild.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities for energy rehabilitation of typical single family house in Belgrade—Case study

Abstract: Paper presents a case study of refurbishment with energy efficiency upgrade of a family house in Belgrade. Analyzed building is a typical representative of family housing stock, based on the national typology of residential buildings, developed during TABULA project, which resulted in definition of models for energy efficiency upgrade and recommendations for reconstruction of each housing type. In this paper possibilities of application of these principles in a real life situation are presented, and several op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…On the other hand, some types are represented in a similar manner in both methodologies (C1, D1, E1). For these types, which both have great local and national representativeness, some more complex improvement scenarios should also be investigated, taking into account their more detailed characteristics [39,40].…”
Section: Comparison Of the Results Of Two Applied Methodsmentioning
confidence: 99%
“…On the other hand, some types are represented in a similar manner in both methodologies (C1, D1, E1). For these types, which both have great local and national representativeness, some more complex improvement scenarios should also be investigated, taking into account their more detailed characteristics [39,40].…”
Section: Comparison Of the Results Of Two Applied Methodsmentioning
confidence: 99%
“…This method, apart from changing the thermal characteristics of an envelope, changes the shape factor and increases its useful living space, enabling the redefinition of the existing apartments of minimal dimensions and outdated and rigid spatial organization [31]. Based on previous results, it can be concluded that an increase in the number of floors reduces energy use for heating per square meter, because it increases the share of apartments situated in the central part of the building (as seen by the height of the building), which have better energy performance of dwellings on the ground and the last floor [32]. According to previous research focusing on the impact factors of a building's shape on final building energy use, correlations exist between the size and shape of the non-heated staircase area and the overall size and shape of the building in the context of total energy consumption for heating [33].…”
Section: Various Aspects Of the Complex And Integrated Refurbishment ...mentioning
confidence: 99%
“…The focus of this research is to investigate a more complex approach based on the application of volumetric additions to the volume of a building. This method, apart from changing the thermal characteristics of an envelope, changes the shape factor and increases its useful living space, enabling the redefinition of the existing apartments of minimal dimensions and outdated and rigid spatial organization [32]. Based on previous results, it can be concluded that an increase in the number of floors reduces energy use for heating per square meter, because it increases the share of apartments situated in the central part of the building (as seen by the height of the building), which have better energy performance of dwellings on the ground and the last floor [33].…”
Section: Various Aspects Of the Complex And Integrated Refurbishment ...mentioning
confidence: 99%